A three-country analysis of the gut microbiome indicates taxon associations with diet vary by taxon resolution and population - Khatib, Lora; Song, Se Jin; Dilmore, Amanda H.; Sanders, Jon G.; Brennan, Caitriona; Hernandez, Alejandra Rios; Myers, Tyler; Oles, Renee; Farmer, Sawyer; Cowart, Charles; Birmingham, Amanda; Diaz, Edgar A.; et al. (mSystems, 2025)
An analysis of fecal microbiome data from individuals in the United States, United Kingdom, and Mexico shows that associations with dietary components vary both by country and by level of resolution (i.e., genus and strain). Our work sheds light on why there may be conflicting reports regarding microbial associations with diet, disease, and health.